Internalization of Human Values in Physics Learning through a Love-Based Curriculum to Build Environmentally Caring Character - Nurhikma Syam; Heru Kuswanto; Yusman Wiyatmo (FKIP - Universitas Riau, 2026)
The global environmental crisis demands a fundamental transformation in science education, shifting from mere cognitive knowledge transfer to a medium for holistic character formation. This conceptual article examines the urgency of internalizing human values such as empathy, compassion, and justice into physics learning. The author proposes a